Hubungan Umur Ibu, Jarak Kehamilan dan Status Anemia Ibu terhadap Kejadian BBLR di Rumah Sakit Umum Daerah (RSUD) Provinsi Sulawesi Tenggara - Setiawati, Rachmi; Kusumawati, Evi (Jurnal Gizi Ilmiah, 2016)
Low birth weight (LBW) babies are babies who when born weigh less than 2,500 grams. Many factors influence the incidence of LBW, including maternal pariety, the distance between pregnancy and maternal anemia status. This study aims to determine the risk factors for maternal age, birth spacing and maternal anemia status on the incidence of LBW in the Regional General Hospital (RSUD) of Southeast Sulawesi Province. This research was conducted on 6 – 12 August 2008 in the midwifery nursery and delivery room at the Southeast Sulawesi Provincial Hospital. Sampling was carried out using a total sampling technique with a case control approach with criteria for mothers who gave birth to the second pariety or more so that the total sample was 117 people and control was 117 people. Data were collected using a data collection form. From the results of the study of 117 samples using the ODS ratio (OR), the value of the upper limit (Upper Limit) and the lower limit (lower limit) showed that there was no relationship between maternal age, birth spacing and anemia status of pregnant women on the incidence of LBW, where the OR factor was the risk between maternal age and the incidence of LBW is 1.037, Ul = 1.8 and LL = 0.052, the risk factor between birth spacing and the incidence of LBW is OR = 1, UL = 8.5 and LL = 0.11 and for anemia status of pregnant women shows OR = 1.419, UL = 7.235 and LL = 0.28. From the results of the study concluded that the prevalence of LBW births was 13.74% and the prevalence of LBW births was 83.40%, with mothers aged 18-42 years, both giving birth to LBW and BBLN. Birth spacing is at risk not only for LBW babies but also for LBW babies and the maternal anemia status is in two categories, namely anemia and non-anaemia, both in LBW babies and LBW babies. maternal anemia status on the incidence of LBW. Suggestions to related agencies to provide knowledge in the form of counseling about the influence of age, birth spacing and anemia status to mothers regarding things that can be risk factors for the incidence of LBW so that the incidence of LBW can decrease in the following year.